Comment on Janjua T K , et al. (J Pak Med Assoc. 74(10), 1836–1842, October 2024) Enhancing cancer care through addressing a neglected pillar: A narrative review on quality of life in Pakistani patients - Abeeha Chaudhry; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2025)
Dear Editor, We read with great interest the recentlypublished review, "Enhancing Cancer Care throughAddressing a Neglected Pillar: A Narrative Review on Quality of Life in Pakistani Patients."1 While the reviewhighlights critical challenges faced by cancer patients inPakistan, it omits an essential component of improvingtheir quality of life (QoL): cancer rehabilitation. Asubspecialty of Physical Medicine and Rehabilitation, cancer rehabilitation is a proven evidence-basedapproach in optimizing cancer survivors’ physical,cognitive, and psychosocial well-being. Its omission reflectsa broader issue in developing countries like Pakistan, whereawareness, accessibility, and implementation of cancerrehabilitation remain limited. Factors that contribute to thecurrent gap in cancer rehabilitation in Pakistan include thefocus on curative rather than preventive treatment and theoverlooking of quality of life measures. The review primarilydiscusses surgical and chemotherapy outcomes. Still,holistic cancer care extends beyond these interventions toinclude both prehabilitation - preemptively enhancing apatient’s resilience before treatment - and rehabilitation - restoring function after cancer therapy2-4